Critical Appraisal of Female Consciousness in Anita Desai’s The Fire on The Mountain - Dhobi, Saleem (Patan Pragya, 2024)
This paper assesses the consciousness of female characters who represent women in Indian society. By using the feminist perspective, Desai’s work, Fire on the Mountain is analyzed to explain why and how women suffer oppression, confinement, slavery and obedience in marriage system that is guided by the principles of patriarchy. The novel portrays Nanda Kaul’s consciousness that is missing in the beginning but gradually confinement, oppression and exploitation teach her to become aware of her individuality. Her life is deeply impacted by societal limitations and patriarchal norms and values. The sufferings lead her to seeking for solitude and peace that is possible in the wilderness. Finally, her consciousness of being an individual with personal feelings and emotions causes transition in Nanda’s life. Her life journey demonstrates the course of women in the marriage institution in patriarchy as depicted in the novel. The exploration of female consciousness by analyzing diverse modes of Nanda’s life implies the consciousness that comes to those who contemplate on their existence and subjectivity ignored in the world controlled and led by men. The subjugation of female characters represents the subordinated life of women in Indian society. When women begin to question the system created for the vested interests of men, they are likely to understand the discriminatory structure in which women are mostly on the margin. By using the approach to content analysis, the paper has been accomplished highlighting the female consciousness in the novel.